Meningkatkan Green brand equity Melalui Green satisfaction dan Customer engagement pada Tamu Hotel di Indonesia - Rini, Gilang Puspita (STIE Widya Manggala, 2024)
Customer awareness regarding environmental damage is increasing. For this reason, this research discusses how to increase green brand equity in green hotels in Indonesia. The aim of this research is to examine the role of green satisfaction and customer engagement in increasing green brand equity by developing a theoretical research framework. A total of 156 respondents were collected, and after carrying out multiple linear regression analyses, it can be seen that the antecedent of green brand equity is customer engagement. Meanwhile, another variable in this research which was also studied, namely green satisfaction, apparently had no effect on the rise and fall of green brand equity in green hotels. This study contributes to future research on green hotels and other research that pays attention to environmental conservation.